Gastroenterological safety of IL-17 inhibitors: a systematic literature review. Issue 2 (1st February 2022) - Caron, Bénédicte; Jouzeau, Jean-Yves; Miossec, Pierre; Petitpain, Nadine; Gillet, Pierre; Netter, Patrick; Peyrin-Biroulet, Laurent
ABSTRACT: Introduction: Interleukin 17 is a proinflammatory cytokine considered to play a significant role in the immunopathogenesis of many chronic immune-mediated disorders. Interleukin 17 inhibitors provide an excellent treatment option for patients with psoriasis, psoriatic arthritis, or ankylosing spondylitis. However, Interleukin 17 inhibitors have been suspected of worsening or triggering new-onset inflammatory bowel disease. Areas covered: A literature search was conducted until March 2021 to investigate reporting prevalence, and characteristics of all gastroenterological adverse events in patients treated with Interleukin 17 inhibitors. One hundred and six clinical randomized trials were included, involving 40, 053 patients. Inflammatory bowel disease cases were reported in 0.4% of patients exposed to Interleukin 17 inhibitors. The most frequent other gastrointestinal adverse events were diarrhea (2.5%), nausea or vomiting (0.7%), and gastroenteritis (0.2%). Sixty-one uncontrolled or retrospective studies were included, involving 16, 791 patients. Sixty (0.36%) inflammatory bowel disease cases were reported, 0.6% of patients reported other gastrointestinal adverse events. Expert opinion: Interleukin 17 inhibitors are safe and effective in the treatment of psoriasis, psoriatic arthritis, and ankylosing spondylitis. Low incidence rate of developing new-onset inflammatory bowel disease or exacerbating preexisting inflammatory bowel disease with anti-IL-17 agents has been reported. Clinicians should be aware of the possibility of these concerns when considering this therapy.